2014
DOI: 10.1002/ejoc.201301394
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Synthesis and Antimalarial Activity of 1,2‐Dioxane‐4‐carboxamides

Abstract: We recently proposed 3‐methoxy‐4‐methoxycarbonyl‐1,2‐dioxanes 3 as promising scaffolds enabling access to potential antimalarial drugs. We present here an optimized two‐step synthesis of 3 characterized by high yields, simple work‐up procedures and high diastereoselectivity allowing us to readily prepare 3 on multigram scale. The versatility of the 1,2‐dioxane scaffold was demonstrated by our generation of a new family of 1,2‐dioxane‐4‐carboxamides 8a–h and the realization of their in vitro activities against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 57 publications
(23 reference statements)
3
20
0
Order By: Relevance
“…In order to test the generality of the mechanism of action of 3-methoxy-1,2- dioxane scaffold16171819, we selected the active compound 4a (Fig. 1), a recently developed synthetic analogue of 2 , to reproduce the experiment of interaction with heme-Fe II -Cl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to test the generality of the mechanism of action of 3-methoxy-1,2- dioxane scaffold16171819, we selected the active compound 4a (Fig. 1), a recently developed synthetic analogue of 2 , to reproduce the experiment of interaction with heme-Fe II -Cl.…”
Section: Resultsmentioning
confidence: 99%
“…The new synthetic derivatives showed in vitro antimalarial activity on Pf CQ-resistant strains comparable to that of the natural leads. Computational and SAR studies performed on the new series of synthetic 1,2-dioxane derivatives indicated that, as in the case of plakortins, the antimalarial activity is related to their ability to react with Fe II generating carbon centered radicals (in this case at C3 and/or at C6 alkyl chain)16171819. Nevertheless, the reaction of 4a with FeCl 2 did not evidence any product whose formation could be related to the antimalarial activity16.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…To investigate the role of the C4 amino-imidazole chain in determining the antimalarial activity of compounds 9a-c (the amido-imidazole analogue of 9a was inactive), 9 compound 9j was synthesized. In agreement with previous SARs, 7-9 its complete loss of activity conrmed that the presence of at least one butyl chain at C3 is necessary for antimalarial activity (9j vs. 9a, Table 1).…”
Section: Structure-activity Relationships (Sars) Studiesmentioning
confidence: 99%
“…In this regard, the observations that replacing all the n-butyl groups by methyl [7][8][9] or propyl 12 chains led to virtually inactive molecules, were especially meaningful. Moreover, the 3D-SAR study proved the active role of the C4 substituent in determining the antimalarial activity, allowing us to obtain IC 50 on the chloroquine resistant (CQ-R) strain in the low micromolar range and, at the same time, very low toxicity against human cells.…”
mentioning
confidence: 99%